Recent advances in transition metal-catalyzed Csp2-monofluoro-, difluoro-, perfluoromethylation and trifluoromethylthiolation - Landelle, Grégory; Panossian, Armen; Pazenok, Sergiy; Vors, Jean-Pierre; Leroux, Frédéric R (Beilstein journal of organic chemistry, 2013)
In the last few years, transition metal-mediated reactions have joined the toolbox of chemists working in the field of fluorination for Life-Science oriented research. The successful execution of transition metal-catalyzed carbon–fluorine bond formation has become a landmark achievement in fluorine chemistry. This rapidly growing research field has been the subject of some excellent reviews. Our approach focuses exclusively on transition metal-catalyzed reactions that allow the introduction of –CFH 2 , –CF 2 H, –C n F 2 n +1 and –SCF 3 groups onto sp² carbon atoms. Transformations are discussed according to the reaction-type and the metal employed. The review will not extend to conventional non-transition metal methods to these fluorinated groups.